Blockchain in Land Registry - Amri, Fauzi; Sihombing, Poltak; Efendi, Syahril (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Blockchain technology that is increasingly developing can be a solution to land disputes. By designing a land title certificate system based on Blockchain technology, which has complete verification and recording of data history. So that it can help the government’s efforts in Agrarian Reform. This research resulted in a system of recording of data history of Land Certificate. that can prove the Blockchain concept where every change that occurs in land title certificate data can be recorded, and distributed to all participants involved in the system.